2011
DOI: 10.1002/stc.481
|View full text |Cite
|
Sign up to set email alerts
|

Guided waves for the health monitoring of sign support structures under varying environmental conditions

Abstract: Guided ultrasonic waves are increasingly used in all those structural health monitoring applications that benefit from built-in transduction, moderately large inspection ranges, and high sensitivity to small flaws. The wavebased structural health monitoring of complex or thick structures can be difficult because of factors such as simultaneous propagation of many modes, large number of overlapping reflections, and mode conversion. Moreover, if the structures are subjected to environmental changes, variations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Overall the SHM paradigm presented here and elsewhere [12] seems to be adequate to the detection of damage that is relatively small compared to the size and the complexity of the structure. Improvement should be made in order to mitigate the effects of variable boundary conditions as the monitoring algorithm underperforms when the boundary conditions are not uniform.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Overall the SHM paradigm presented here and elsewhere [12] seems to be adequate to the detection of damage that is relatively small compared to the size and the complexity of the structure. Improvement should be made in order to mitigate the effects of variable boundary conditions as the monitoring algorithm underperforms when the boundary conditions are not uniform.…”
Section: Discussionmentioning
confidence: 77%
“…Then the peak-to-peak (ppk) amplitude, variance (var), root mean square (rms), crest factor (cf), and k-factor (kf) were calculated for each time-windowed signal. These features were selected based upon the outcomes of previous researches of the authors' group [1,2,12].…”
Section: The Laboratory Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Laory et al evaluated damage detectability and detection time of two model‐free damage detection methods, that is, the moving principal component analysis method and the robust regression analysis method, considering the temperature effect; the evaluation is conducted in a numerical analysis based on a railway truss bridge in Germany, and three numerical damage cases were simulated in the form of stiffness losses at the top and bottom chords of the truss bridge model; results show that the two methods are complementary and have different seasonal variation sensitivities. Zhu and Rizzo presented a damage detection method for truss welded joints based on guided ultrasonic waves; cracks of various sizes near the weld toe of a joint in an experimental truss are simulated under varying environmental effects; it is found that the combination of damage features can increase the damage sensitivity and decrease environmental effects including the varying temperature and the boundary condition.…”
Section: Recent Progress On Damage Identification Methods For Truss Bmentioning
confidence: 99%